Biophysical Investigation of GpIbα Binding to Thrombin Anion Binding Exosite II - Sabo, T. Michael (2009)
Substrates and cofactors of the serine protease thrombin (IIa) employ two anion binding exosites (ABE-I and II) to aid in binding. On the surface of platelets resides the membrane bound receptor complex GpIbα/β-GpIX-GpV. IIa’s ABE-II is proposed to interact with an anionic portion of GpIbα which enhances IIa cleavage of PAR-1 and subsequent activation of platelets. In the current work, 1D and 2D NMR, analytical ultracentrifugation (AUC), and hydrogen deuterium exchange (HDX) coupled with MALDI-TOF MS were performed to further characterize the features of binding to IIa’s ABEs. The described work builds upon investigations performed in a prior study with fibrin(ogen)’s γ′ peptide and IIa (Sabo, T. M., Farrell, D. H., and Maurer, M. C. (2006) Biochemistry 45, 7434–7445). 1D line broadening NMR ((1)H and (31)P) and 2D trNOESY NMR studies indicate that GpIbα D(274)-E(285) interact extensively with the IIa surface in an extended conformation. AUC demonstrates that both GpIbα (269–286) and γ′ (410–427) peptides interact with IIa at 1:1 stoichiometry. Comparing the HDX results to the ABE-I targeting peptide hirudin (54–65), the data implies that GpIbα (269–286), GpIbα (1–290), and γ′ (410–427) are indeed directed to ABE-II. The ABE-II binding fragments reduce HDX for sites distant from the interface suggesting long range conformational effects. These studies illustrate that GpIbα and γ′ target ABE-II with similar consequences on IIa dynamics, albeit with differing structural features.